(untitled) (Orfeu, 2020)
This paper presents three walks whose intention were either the listening of a region of Rio de Janeiro as well as its photographic and phonographic takings, therefore making a poetic analysis of the material. In order to support the analysis, a bibliographic revision relating concepts from urban mobility and listening is made. Taking the thesis of Steven Feld (2015) as starting point, in which the sound is understood as an object for the social tissue’s knowledge, the sonority of the visited places is taken as focus for the discussion. Those places can be understood, by their urban characteristics in the context of the contemporary city, as negative spaces (Milton Santos, 1994) or opaque spaces(Francesco Careri, 2017) – and those concepts will have significant repercussions on the incursions´s narratives. The obtained material intends to interrelate the textual and photographic registers with the sounded register in order to contextualize its listening. In spite of one of the incursions has resulted on a sound installation, the material is previous any artistic realization in a work format and either its analysis as its listening are part of a current compositional process or, at least, of a sound/musical creation from field recordings.